Harmonising with heaven and earth : reciprocal harmony and Xunzi’s environmental ethics - Chua, Jonathan Yi (2022)
Xunzi’s philosophy provide a rich resource for understanding how ethical relationships between humans and nature can be articulated in terms of harmony. In this paper, I build on his ideas to develop the concept of reciprocal harmony, which requires us to reciprocate those who make our lives liveable. In the context of the environment, I argue that reciprocal harmony generates moral obligations towards nature, in return for the existential debt that humanity owes towards heaven and earth. This can be used as a normative basis for an environmental ethic that enables humanity and nature to flourish together.